The social life of historical neighbourhoods: case study of a Middle Eastern city, Shiraz - Farahani, Leila Mahmoudi; Lozanovska, Mirjana (Journal of Architecture and Urbanism, 2015)
Historic neighbourhoods have usually shaped on an organic structure in regard to their residents’ requirements. Due to the limitations in mobility, historical neighbourhoods were usually able to perform as a small city comprising all the elements required for satisfying physical, social, and cultural needs. This paper seeks to explore the patterns of social life in the traditional settlements in Shiraz and investigate the elements that have shaped the social life of these neighbourhoods. Exploring the social structure of historic neighbourhoods may introduce new approaches to the design of contemporary suburbs and neighbourhoods in terms of their vitality and social life. A review of the literature and comparing it to the historical core in Shiraz shows that there are five contributing factors to the social life of historic neighbourhoods in Shiraz, including density, human scale development, walkability, mixed land-use and qualities of public spaces. Exploring the features of public places and communal facilities indicates that the fine social performance of these settlements is rooted in their compatibility and adaptability to the environment, the residents’ requirements and culture.